2016
DOI: 10.4103/1119-3077.175972
|View full text |Cite
|
Sign up to set email alerts
|

Topical-intracameral anesthesia in manual small incision cataract surgery: A pilot study in a Tertiary Eye Care Center in Africa

Abstract: The mean pain score in this study is low. There is no correlation between perception of pain with gender or age. Surgeons experience is excellent in most of the cases. This method of anesthesia in MSCIS is adequate for patient's comfort and safe cataract surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“… 4 Since MSICS involves increased handling of tissues such as conjunctiva and sclera, and potentially increased iris touch in comparison to phacoemulsification, peribulbar anesthesia has remained the most common mode of anesthesia for the procedure. 5 9 10 This is even though multiple authors and reviews have shown the effectiveness and relative painlessness of STA. 9 14 15 16 27 This could be because STA is still not commonly performed in many training centers and involves the learning of a slightly different and newer method of administering anesthesia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 4 Since MSICS involves increased handling of tissues such as conjunctiva and sclera, and potentially increased iris touch in comparison to phacoemulsification, peribulbar anesthesia has remained the most common mode of anesthesia for the procedure. 5 9 10 This is even though multiple authors and reviews have shown the effectiveness and relative painlessness of STA. 9 14 15 16 27 This could be because STA is still not commonly performed in many training centers and involves the learning of a slightly different and newer method of administering anesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…Topical anesthesia is the most common method of anesthesia for phacoemulsification cataract surgery. 1 2 3 For manual small incision cataract surgery (MSICS), which is a worthy alternative to phacoemulsification and has been endorsed not just as the most appropriate technique in developing countries 4 5 6 7 but also advocated for inclusion in the surgical curriculum in the Western world, 8 peribulbar anesthesia remains the norm in the majority of cases. 5 9 10 Peribulbar anesthesia is a relatively blind and invasive technique with potentially dangerous side effects such as globe perforation, orbital hemorrhage, and brainstem anesthesia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subtenon was superior to intravenous Fentanyl for perioperative anaesthesia in infants undergoing cataract surgery measured by cries pain score [33] . In a hospital based case series study to evaluate the efficacy and safety profile of the use of aqueous topical/intracameral anesthesia in manual small incision cataract surgery, Uche et al [34] reported that the mean pain score in this study was low, there was no correlation between perception of pain with gender or age and surgeons experience was excellent in most of the cases.…”
Section: Comparison Of Pain Scorementioning
confidence: 99%